Decarbonization potential of on-road fuels and powertrains in the European Union and the United States: a well-to-wheels assessment. Issue 19 (1st September 2022) - Cai, Hao; Prussi, Matteo; Ou, Longwen; Wang, Michael; Yugo, Marta; Lonza, Laura; Scarlat, Nicolae
Abstract : Life-cycle analysis is essential to assessing the greenhouse gas impacts and decarbonization potential of transportation fuels and vehicle powertrains. Abstract : Transportation is fundamental for any modern economy, but its growing energy demand and the related climate impact call for urgent action. Life-cycle analysis (LCA) is a suitable approach to assessing the greenhouse gas (GHG) performance and decarbonization potential of transportation fuels and vehicle powertrains. Here, we assessed well-to-wheels (WTW) GHG emission reductions for a wide set of light-duty vehicle fuel and powertrain technologies used in the European Union (EU) and the United States (U.S.) for their decarbonization potential. We focused on the similarities and differences of the results and the underlying methodologies and data of the two analyses. We evaluated the decarbonization potential of new fuel–vehicle systems in Europe and the United States in comparison to the baseline petroleum gasoline and diesel vehicles in each market. For the transportation fuels examined in both regions, waste-to-fuel technologies and drop-in renewable diesel fuels (biofuels) produced from residues offer the biggest opportunities for reducing per-energy-unit GHG emissions, but may be limited in scale-up potentials given feedstock availabilities, qualities, and logistics challenges. The potential benefits of electricity and hydrogen as fuels span a wide range, determined by the primary energy source and the potential deployment of carbon capture and sequestration technologies. From a tank-to-wheels perspective, electric powertrains, with higher energy efficiency than internal combustion engines, provide incontrovertible evidence of GHG savings. For vehicle–fuel combined systems, the per km WTW results from GREET are generally higher than the JEC estimates, owing to greater vehicle fuel consumption attributable to larger vehicle sizes and more aggressive driving cycles in the U.S. This paper highlights key drivers of WTW fuel–vehicle system GHG emissions as well as opportunities and limitations to decarbonize light-duty transportation in Europe and the United States with promising alternative fuel production and vehicle powertrain technologies. Results show that major solutions in both regions are aligned, despite certain differences in the methodologies and results of the WTW analyses. As well as informing optimal selection of fuel and powertrain technologies for future vehicles, these findings are also useful in informing how existing vehicles can best be decarbonized through the use of renewable fuels and advanced powertrain technologies.